Adyghe (Circassian) Religiosity and its Reproduction in Contemporary Prose - A. Kirzhinova, S.; K. Bzegezheva, L.; K. Bolokova, M.; N. Huako, F. (International Journal of Engineering and Technology, 2018)
Article considers Adyghe (Circassian) religiosity and its reproduction in contemporary prose. Conducted study and a variety of problems in this case are rare, besides, almost complete cancellation of any research activity in today's Russia is known. And the problems are not studied enough. Therefore, the relevance of the selected topic is undoubtedly important, and we are developing it using a number of analytical and synthetic methods inherent in humanitarian knowledge. In the course of research, we established that the fact that both religions common today (Christianity, Islam) are not at all sources of interethnic difficulties, and concluded that the state must strive to support the existing religious branches (in particular, Islam and Christianity). The relevance of this work is that the problems in this field are too little studied, and our research provides new data, as well as a new look at this topic.Â Â